Paralegals as Agents of Legal Empowerment: Bridging Access to Justice and Maqasid al-Shariah in Rural Indonesia - Fathurrozi, Adi; Sa'ada, Sri Lum'atus; Pujiono, Pujiono (IJoIS: Indonesian Journal of Islamic Studies, 2025)
Access to justice for underprivileged communities remains a persistent challenge in many developing countries, including Indonesia, where economic constraints, limited legal literacy, and restricted access to formal legal institutions hinder the realization of legal rights. While prior studies have examined legal empowerment and access to justice, they largely overlook the integration of Islamic normative frameworks, particularly Maqasid al-Shariah, within empirical community-based practices. This study addresses this gap by examining the role of paralegals as agents of legal empowerment in rural contexts and analyzing how their practices bridge access to justice and maqasid-oriented values. Using a qualitative empirical case study design, this research was conducted in Tlogosari Subdistrict, Bondowoso Regency, involving purposively selected participants. Data were collected through in-depth interviews, participant observation, and document analysis, and analyzed using thematic coding based on the Miles and Huberman model. The findings show that paralegals perform multidimensional roles as legal educators, mediators, and facilitators, prioritizing non-litigation mechanisms, participatory legal education, and community-based strategies. These approaches enhance the availability, accessibility, affordability, and effectiveness of legal services for marginalized groups. Moreover, paralegal practices substantively reflect maqasid principles, particularly in safeguarding life, property, and intellect, thereby extending justice beyond procedural dimensions toward human welfare. This study introduces Islamic Social Justice as a novel framework integrating legal empowerment, access to justice, and Islamic ethical principles, offering a context-sensitive and inclusive model for strengthening equitable legal systems.